2012
DOI: 10.1063/1.4710531
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependent magnetic properties of amorphous FeTaC films

Abstract: We report on the study of thickness and temperature dependent magnetic properties of amorphous FeTaC (t = 20–200 nm) thin films prepared on thermally oxidized Si substrate at ambient temperature. Room temperature coercivity remains constant (∼1.5 Oe) for t between 20 and 50 nm, but increases rapidly (>18 Oe) when t > 50 nm. Also, the shape of M-H loop changes from rectangular to flat loop with increasing film thickness; and at larger thicknesses (>50 nm), the central range of constant slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The coercivity fields (H C ) for 20 and 50 nm samples are found to be 1.5 and 2 Oe, respectively which is a characteristic feature of soft ferromagnetism. By increasing the film thickness (≥ 100 nm), the M − H clearly shows the transcritical loop manifesting the presence of stress induced perpendicular anisotropy during the film deposition [5]. M S is found to increase from 6125 ± 30 Oe to 7740 ± 40 Oe as the film thickness increases from 20 to 200 nm.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The coercivity fields (H C ) for 20 and 50 nm samples are found to be 1.5 and 2 Oe, respectively which is a characteristic feature of soft ferromagnetism. By increasing the film thickness (≥ 100 nm), the M − H clearly shows the transcritical loop manifesting the presence of stress induced perpendicular anisotropy during the film deposition [5]. M S is found to increase from 6125 ± 30 Oe to 7740 ± 40 Oe as the film thickness increases from 20 to 200 nm.…”
Section: Resultsmentioning
confidence: 90%
“…The amorphous nature of those alloys reduces the number of pinning centers which may lead to the spin transfer torque (STT)-driven domain wall motion along with high tunneling magnetoresistance ratio (TMR) [1]. It has been reported that the addition of 20 % metalloid (in this case 'Ta' and 'C') in Fe based FM metal matrix destroys crystallinity and shows enhanced soft magnetic properties [2], [3], [4], [5], [6]. Furthermore, the soft magnetism in Fe based nanocrystalline alloys arises from two-phase microstructure in which fine nanocrystals are embedded in amorphous matrix, resulting a strong intergranular FM exchange coupling [7].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Malinowski et al In this letter, we focus on amorphous FeTaC layer due to its interesting soft ferromagnetic (FM) properties. 17,18 The amorphous soft FM layer reduces the number of pinning centers which may lead to the STT-driven domain wall motion along with high tunneling magnetoresistance ratio (TMR). The transcritical loop along with the stripe domain structure, which are the manifestation of PMA component were reported on FeTaC thin film with thickness of 200 nm.…”
mentioning
confidence: 99%
“…The transcritical loop along with the stripe domain structure, which are the manifestation of PMA component were reported on FeTaC thin film with thickness of 200 nm. 18,19 To shed some more light onto its dynamic magnetic properties, we have further studied this film by using ferromagnetic resonance technique. Though the magnetic anisotropy and Gilbert damping have been studied by FMR technique in several magnetic thin films like Heusler alloys, permalloy, soft magnetic materials and multilayered (FM/antiferromagnetic or non-magnetic/FM) magnetic films for magnetic recording, MTJ and TMR reader applications, most of the reports are limited to single frequency due to the measurements in X-band electron-spin-resonance spectrometer where the cavity resonates at particular frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation